Group concept mapping to develop a salon-based HPV self-collection intervention - Kelly N. B. Palmer; Namoonga M. Mantina; Adebola Adegboyega; Itunu O. Sokale; Kathleen Pryor; Azaria Suero-Davis; Trevon Brooks; Jennifer Hatcher (Cancer Causes & Control, 2025)
Background Black women in the US face higher cervical cancer mortality rates due to delayed diagnoses linked to lower screening rates. Contributing factors include provider bias, costs, and limited access, particularly affecting women aged 40–64. While innovative approaches like clinical and home-based HPV self-collection exist, equitable dissemination remains challenging. Distributing HPV self-collection kits in unconventional sites like hair salons may offer a solution. Using concept mapping, we gathered community insights to design a salon-based cervical cancer screening intervention. Methods We employed groupwisdom™ and REDCap platforms for community-based participatory intervention development. Participants included members of the Black Community Advisory Council of Tucson (Black CACTus), comprising hairstylists ( n = 3), salon clients ( n = 4), and healthcare providers( n = 3), all identifying as Black women aged 23–53. Concept mapping included: 1) Brainstorming statements, 2) Sorting statements into thematic clusters, 3) Rating importance and feasibility, 4) Reviewing the cluster map, and 5) Evaluating a draft intervention. Results Brainstorming produced 39 statements, forming six clusters: 1) Program Promotion, 2) Insurance, Cost & Benefits, 3) Communication Considerations, 4) Information and Education, 5) Overall Logistics and Process, and 6) Sample Collection. Communication Considerations and Sample Collection were rated most important, with Communication Considerations also ranking highest for feasibility. Communication Considerations, Information and Education, and Sample Collection were the highest rated when importance and feasibility were considered together. Conclusions Engaging community perspectives is essential for adapting cancer screening from clinical settings to community spaces like hair salons. This collaborative concept mapping approach identified strategies to enhance cervical cancer screening access and uptake among Black women.

Seasonal and longitudinal dynamics of DOM within headwater streams of a tropical evergreen forest - Samantha N. Sullivan; Jennifer C. Bowen; Louis A. Kaplan; Rose M. Cory; Patrick G. Hatcher (Water Research, 2025)

Building capacity for collaborative research between basic scientists and underrepresented communities in cancer research - Namoonga M. Mantina; Juan Contreras; Monica Yellowhair; Cynthia Miranti; Jennifer Hatcher (Cancer Causes & Control, 2023)